Analisis Perbandingan User Experience Shopee & TikTok Shop dengan System Usability Scale dan Usability Testing - Alfredo Herijanto; Andeka Rocky Tanaamah (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Shopee and TikTok Shop are companies engaged in online shopping, commonly referred to as e-commerce. With the rapid advancement of technology, both platforms continue to grow and compete by offering features that aim to enhance user convenience. Among the two, Shopee demonstrates certain advantages over TikTok Shop. This raises the question of what factors contribute to Shopee’s superiority whether it is due to its product recommendation algorithm or overall usability. This study aims to examine the accuracy of product recommendation algorithms and evaluate usability using the System Usability Scale (SUS) and the ISO 9241-11 usability framework. The results show that the average SUS score for Shopee is 69.50, placing it in the